Technology readiness, customer perceived value, customer information satisfaction and behavioral intention on tablet-based menu ordering experience / Muhammad Izzat Zulkifly - Zulkifly, Muhammad Izzat (Institute of Graduate Studies, UiTM, 2017)
It is a common practice among restaurateurs to provide menu cards as a medium of communication to speak about their menu items. Many limitations have been identified from the use of this method of menu ordering such as customer indecision and other forms of service failures. Tabletbased menu ordering system which is „self-service” in nature is gaining popularity among restaurants due to its capacity to handle descriptive menu, other information and illustration as well as other interactive options and many other benefits. The success of this system depends on how restaurants balance the use of technology and human touch. Too much dependency on technology would take away the human-touch value which is important in a foodservice operation. Not much is known about Malaysian customers” technology readiness and how they perceived the value offered by this system, thus it is difficult to figure out the effectiveness of the system based on their information satisfaction on the menu ordering experiences which will then influence customers” behavioural intention. This study empirically investigates the causal relationship between technology readiness, customer perceived value, customer information satisfaction and behavioural intention towards the tablet-based menu ordering system…